2018
DOI: 10.1093/jxb/ery429
|View full text |Cite
|
Sign up to set email alerts
|

SiSTL1, encoding a large subunit of ribonucleotide reductase, is crucial for plant growth, chloroplast biogenesis, and cell cycle progression in Setaria italica

Abstract: A ribonucleotide reductase large subunit mutant isolated from Setaria italica had a Gly737 to Glu substitution in the C-terminus of the protein and exhibited growth retardation and striped leaves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Apart from tvt1‐m1 in maize, a frameshift mutation of the ribonucleotide large subunit (R1) gene, most mutants of the R1 gene identified in higher plants are caused by missense mutations that result in the substitution of a single amino acid. For example, the cls8 mutant in Arabidopsis, the v3 mutant in rice, the sistl1 mutant in S. italica (foxtail millet) and tvt1‐R in maize were caused by Gly 718 Ala, Gly 291 Ser, Gly 371 Glu and Arg 277 His, respectively (Garton et al., 2007; Tang et al., 2019; Xie et al., 2020; Yoo et al., 2009). svstl1 exhibited growth retardation as well as a bleached and rolled leaf phenotype in flag leaves at the heading stage under normal growth conditions (Figure 1c,d; Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from tvt1‐m1 in maize, a frameshift mutation of the ribonucleotide large subunit (R1) gene, most mutants of the R1 gene identified in higher plants are caused by missense mutations that result in the substitution of a single amino acid. For example, the cls8 mutant in Arabidopsis, the v3 mutant in rice, the sistl1 mutant in S. italica (foxtail millet) and tvt1‐R in maize were caused by Gly 718 Ala, Gly 291 Ser, Gly 371 Glu and Arg 277 His, respectively (Garton et al., 2007; Tang et al., 2019; Xie et al., 2020; Yoo et al., 2009). svstl1 exhibited growth retardation as well as a bleached and rolled leaf phenotype in flag leaves at the heading stage under normal growth conditions (Figure 1c,d; Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…sistl1 exhibited growth retardation as well as a striped leaf phenotype and decreased chloroplast biogenesis. However, the relationship between the three genes in the RNR large subunit family remains enigmatic (Tang et al., 2019). An examination of the S. viridis genome revealed that R1 is encoded by three genes ( SvSTL1 , SvSTL2 and SvSTL3 ) (Figure 6a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to our continuing efforts, positional cloning in Setaria is now practicable using “SSR41” and “Yugu1” EMS mutants as plant materials. To date, map-based cloning has been used to characterize at least eight S. italica genes, including SiMADS34 ( Hussin et al, 2021 ), DPY1 ( Zhao et al, 2020 ), SiSTL1 ( Tang et al, 2019 ), SiSTL2 ( Zhang et al, 2018a ), SiYGL1 ( Li et al, 2016 ), SiYGL2 ( Zhang et al, 2018b ), Loose Panicle1 ( Xiang et al, 2017 ), and SiAGO1b ( Liu et al, 2016 ). These studies illustrate that “SSR41” and “Yugu1” are suitable germplasm resources for forward genetics and positional cloning research on Setaria .…”
Section: Discussionmentioning
confidence: 99%
“…We propose that “SSR41” is an ideal genotype to match to “Yugu1” mutants to construct mapping populations, because “SSR41” is morphologically similar to, but highly genetically divergent from, “Yugu1”. To data, several genes of S. italica have been cloned using “SSR41” and the corresponding “Yugu1” mutant, including DPY1 ( Zhao et al, 2020 ), SiAGL1b ( Liu et al, 2016 ), SiSTL1 ( Tang et al, 2019 ), SiSTL2 ( Zhang et al, 2018a ), SiYGL1 ( Li et al, 2016 ), and SiYGL2 ( Zhang et al, 2018b ). In addition, “SSR41” is an elite cultivar with high yields, good grain quality, resistance to diverse diseases, and wide local adaptability, so it will be useful for breeding and crop improvement.…”
Section: Introductionmentioning
confidence: 99%